Estudio químico y evaluación de la actividad antimicrobiana del aceite esencial de Myrcianthes rophaloides Mc Vaugh - Maldonado Rodríguez, María Elena (2006)
The study of the chemical composition of the essential oil of Mircianthes rhopaloides McVaugh, Myrtaceae family, carried out by means of the technique of gas-chromatography coupled to mass-spectometer, allowed to identify that the essential oil contains a mixture of the following component main mono- and sesquiterpenes: Linalol, Eucaliptol, D – Limonene, ‰ Terpineol. In smaller proportion they are: 4 Terpineol; cis Mirtanol, Cariophylene; - Cariophylene ;  Cadinene, Spatulenol. The study of antibacterial activity, evidences the activity of the essential oil of Mircianthes rhopaloides Mc Vaugh, Myrtaceae family, against Streptococcus mutans, Streptococcus pyogenes mainly, and in smaller proportion against Staphylococcus aureus, Staphylococcus epidermidis. No activity has been shown against Eschericia coli and Candida albicans